Performance of adobe vaults strengthened with LC-TRM: an experimental approach - Sadeghi, Neda H. (2022)
Due to the vulnerability of vaulted adobe buildings during the past earthquakes, it is crucial for such building typology to be evaluated in terms of seismic capacity. This paper deals with the seismic performance of historic vaulted adobe construction in adobe houses, typical from the city of Yazd, Iran. To this end, six 1:3 scaled adobe vaults were analyzed experimentally aiming at estimating their structural performance. The tests were performed in loading-unloading steps of increasing amplitude of an imposed vertical displacement at 30% of span. The tests were carried out in two unstrengthened and four strengthened adobe vaults. Vaults were strengthened with a low-cost textile reinforced mortar (LC-TRM), where a low-cost fiber-glass mesh is covered with an earth-based mortar. Two adobe vaults were strengthened at intrados and the other two at extrados. The experimental results show that the vaults behavior is enhanced due to the LC-TRM application, with respect to the unstrengthened vaults. A significant increase of the load-carrying capacity and also an important improvement in ductility was evident. In addition, new failure mechanisms were observed for the strengthened vaults when compared with the formation of the typical four-hinge mechanism of unstrengthened vaults.